The Euro in Historical Comparison to the Ruble and the Influence of Overconfidence. (European Journal of Marketing and Economics, 2019)
This paper deals with the structured comparison of the former ruble monetary union with the euro currency area. As a basis, developments in the ruble currency area and in the Eurozone are traced. In a comparison of the central components of the currency areas, similarities, such as the heterogeneity of the states, and differences, for example the role of the central bank and the legal foundations of the currency area, are outlined. Subsequently, the significant historical exit causes of the states from the Soviet Union out of the ruble currency zone are presented. In addition to obvious structural factors, such as the unequal power structure, also practical reasons, such as the insufficient provision of cash for some areas, are considered. Regarding overconfidence, the sub-categories overestimation and overplacement can be detected mainly regarding the behavior of the administration of the former USSR. The third sub-category, overprecision, can primarily be found in the behavior the European Central Bank and their efforts to stabilize the Euro. Based on the findings, the conclusion can be drawn, that there are certain parallels between the two currency areas. However, the available options for action and mechanisms at the political and economic level in the Eurozone today are more wide-ranging than at the beginning of the 1990s in the ruble currency area.